Single‐Site Gold Catalysts on Hierarchical N‐Doped Porous Noble Carbon for Enhanced Electrochemical Reduction of Nitrogen. Issue 12 (20th August 2018) - Qin, Qing; Heil, Tobias; Antonietti, Markus; Oschatz, Martin
Abstract: Electrocatalytic reduction of nitrogen (N2 ) at ambient conditions is an alternative strategy to produce ammonia (NH3 ) to complement the commonly applied Haber–Bosch process. However, the achievement of high Faradaic efficiencies and high NH3 yield is still challenging. Here, Au single sites stabilized on N‐doped porous and highly oxidizing ("noble") carbon catalysts showing excellent performance in N2 electroreduction are reported. At a potential of −0.2 V versus reversible hydrogen electrode, a stable NH3 yield of 2.32 µg h −1 cm −2 is produced at a Faradaic efficiency of 12.3%. Besides, there is no notable fluctuation of Faradaic efficiency and NH3 yield in six‐cycle test, which indicates good stability. This work opens up new insights to improve N2 fixation performance by introducing catalytically active single sites into noble carbon materials for N2 electroreduction. Abstract : Developing efficient N2 reduction reaction (NRR) electrocatalysts is required to improve the performance of N2 fixation by renewable electricity and complement the Haber–Bosch process to meet the future nitrogen‐based fertilizers demands. By using Au single sites stabilized on N‐doped porous noble carbons catalysts, electrochemical NRR with remarkable Faradaic efficiency and NH3 yield is achieved at ambient conditions.